Leadership Characteristics Dalam Asumsi Gender : (Studi Pada Awak Kapal Indonesia) - Ndori, Ahmad; Hermawati, Renny; Utami, Prapti; Sulistiana, Asri Dwi (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2024)
In the maritime industry, the International Maritime Organization (IMO) fully supports gender equality programs. IMO's form of support regarding gender equality is stated in resolution 14 of the Standard of Training Certification and Watchkeeping for Seafarers (STCW) Amendment 2010, which states that IMO supports women to play an active role in the maritime industry, including their active role as ship crew. Male and female crew members have different leadership qualities. This research aims to determine the differences in leadership characteristics of male and female crew members and to determine the relationship between leadership characteristics and gender perspectives on organizational conditions on ships. This research is qualitative research. The approach used in this research is grounded theory. The results of this research lead to the knowledge that differences in the gender of ship crew who are leaders will cause differences in treatment of subordinates or humans in an organization on a ship. At the middle level, the leadership results of male crew members are less effective than female crew members. Meanwhile, the leadership character of male crew members will be maximized when they have full power in the highest position in the organizational structure on the ship.